Case Report: Methylphenidate and venlafaxine improved abdominal nociplastic pain in an adult patient with attention deficit hyperactivity disorder, autism spectrum disorder, and comorbid major depression - Kasahara, Satoshi; Takahashi, Miwako; Takahashi, Kaori; Morita, Taito; Matsudaira, Ko; Sato, Naoko; Momose, Toshimitsu; Niwa, Shin-Ichi; Uchida, Kanji (Frontiers in Pain Research, 2024)
IntroductionNociplastic pain (NP), classified as a third type of pain alongside nociceptive and neuropathic pain, is chronic pain arising from the amplification of nociceptive stimuli through central sensitization, despite the absence of tissue damage, sensory nerve damage, or disease. An important clinical feature of NP is that it is not only associated with pain but also with sensory hypersensitivity to sound and light and cognitive dysfunction, including mood and attention disorders. Recent studies have suggested that depression and developmental disorders, such as attention deficit hyperactivity disorder (ADHD) and autism spectrum disorder (ASD), coexist with NP at high frequency. Additionally, cognitive impairment in individuals with NP may be associated with these psychiatric comorbidities. However, to our knowledge, there are no reports on (1) multidimensional evaluation and diagnostic details of abdominal NP in adults with ADHD/ASD; (2) how ADHD drugs and antidepressants are administered when ADHD and depression coexist with NP; and (3) how central sensitization, brain function, and family relationship problems underlying NP are altered by treatments of ADHD and depression.Case presentationHerein, we present the case of a 51-year-old woman with abdominal NP. She developed severe right lower abdominal pain and underwent a thorough medical examination; however, the physical, medical cause remained unknown, making treatment challenging. Additionally, she took time off work as she began to complain of insomnia and anxiety. She was referred to our pain center, where a diagnosis of depression, ADHD, and ASD was confirmed, and treatment with ADHD medication was initiated. While ADHD medications alone did not yield sufficient improvement, a combination of methylphenidate and the antidepressant venlafaxine eventually led to improvements in abdominal NP, depression, ADHD symptoms, central sensitization, and family relationship issues. During treatment, cerebral blood flow in the anterior cingulate, prefrontal, and parietal cortices also improved.ConclusionThe treatment of comorbid depression is important while treating NP, and venlafaxine may be effective, especially in cases of comorbid ADHD/ASD. Screening for developmental disorders and depression is required in patients with abdominal NP.